Mn(III)-porfirinas como catalisadores biomiméticos: estabilidade térmica e imobilização em vermiculita e sílica gel funcionalizada para hidroxilação de alcanos - Pinto, Victor Hugo e Araujo (2013)
An alternative route for the synthesis of the three isomers of Mn(III) N-metylpyridylporphyrins, MnTM-X-PyPCl5 (X = 2, 3, 4) was developed by the direct methylation of MnT-X-PyPCl (X = 2, 3, 4) with methyl tosylate; this methodology may be adapted for preparing the longer-alkyl-chain analogues. The investigation of the thermal stability of the potent redox modulator Mn(III) meso-tetrakis(N-ethylpyridinium-2- yl)porphyrin chloride (MnTE-2-PyPCl5) showed that the thermal decomposition of MnTE-2-PyPCl5∙11H2O under air occurs in three successive steps: dehydration, dealkylation (ethyl chloride loss) and combustion, to yield Mn oxide as final residue. Heating MnTE-2-PyPCl5∙11H2O up to ~100 ºC leads to dehydration, but with no effect onto the catalytic SOD activity after rehydration/dissolution. Heating the sample at temperatures above 100 ºC leads to dealkylation, which affects catalytic and biological properties. The immobilization of the neutral Mn porphyrins (MnPs) MnT-X-PyPCl (X = 2, 3, 4) covalently onto chloropropyl silica-gel (Sil-Cl) or the cationic MnPs MnTM-X-PyPCl5 (X = 2, 3, 4) electrostatically into sodium vermiculite (verm) yielded stable biomimetic models of cytochromes P450. The resulting materials, Sil-Cl/MnT-X-PyPCl e verm/MnTM-X-PyPCl5 (X = 2, 3, 4), were used as oxidation catalyst for hydroxylation of cyclohexane and adamantane by iodosylbenzene. The heterogeneous systems were more efficient, selective, and oxidatively stable than the homogeneous counterparts, and could be reused three times with no significant loss in efficiency. The use of more drastic conditions (i.e., large excess of PhIO), led to considerable decrease in efficiency, which was partial recovered upon catalyst reuse uner milder conditions, indicating that the support protects the supported MnP against oxidative degradation. The materials efficiently catalyzed the oxidation of cyclohexanol to cyclohexanone, suggesting that the ketone observed during cyclohexane hydroxylation may result, at least partially, from cyclohexanol oxidation. The covalent bond between Sil-Cl and MnPs via N-pyridyl moiety allowed the preparation of efficient and stable catalysts, even with first generation, simple MnPs, such as MnT-X-PyPCl (X = 2, 3, 4). Vermiculite was revealed as a simple and effective support for rapid and qualitative immobilization of cationic MnPs, MnTM-X-PyPCl5 (X = 2, 3, 4). Grinding of the vermiculite-based materials decreased the crystallinity of the systems, which was followed by an increase in the catalytic efficiency of the meta and para isomers verm/MnTM-X-PyPCl5 (X = 3 and 4), but did not affect of the high efficiency of the immobilized ortho isomer (verm/MnTM-2-PyPCl5), whose resistance to oxidative destruction and/or leaching was, additionally, higher than that of the other isomers.